EDUKASI PMT BERBASIS BAHAN HERBAL UPAYA PENCEGAHAN STUNTING DI DESA KEBALEN KECAMATAN BABELAN - Mukaromah, Nahdiyatul (Universitas Mataram, 2025)
Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia, including in Kebalen Village, Babelan District. One innovative effort to prevent stunting is through education on supplementary feeding (PMT) using local herbal ingredients that are rich in nutrients and easily accessible. This program aimed to improve the knowledge and awareness of mothers with toddlers regarding balanced nutrition and the use of herbal ingredients to support child growth. The methods included education sessions, training, and demonstrations on preparing herbal-based PMT, involving 32 mothers as participants. The evaluation results showed a significant improvement in knowledge, with the “good” category increasing from 15.6% to 31.2%, and the “poor” category decreasing from 53.1% to 12.6%. This education also successfully encouraged the practice of providing nutritious and natural food at the household level. In conclusion, herbal-based PMT education is an effective and sustainable strategy for community-based stunting prevention, especially in rural areas.